PENGEMBANGAN KURIKULUM BERBASIS MULTIKULTURALISME DI INDONESIA (LANDASAN FILOSOFIS DAN PSIKOLOGIS PENGEMBANGAN KURIKULUM BERBASIS MULTIKULTURALISME) - Syamsul Bahri (Jurnal Ilmiah Didaktika, 2018)
The curriculum of education may change according times and contextuality of society. Indonesian society is known as a multicultural society, so curriculum development should involve multiculturalism aspect, which is called multicultural curriculum. To strengthen the building of curriculum based on multiculturalism, it is need to develop philosophically and psychologically. The focus of problem in this research is, how is the philosophical and psychological basis of curriculum development based on multiculturalism in Indonesia?? This research is called library research with content analysis method. The data collected is objectively and systematically interpreted. The results of this study indicate the basis of curriculum development based on multicultural philosophically in the form of progressivism, recontruksionism and pancasilais. Psychologically, the development of a multicultural-based curriculum is the implementation of multicultural substance in accordance with the development of students put forward by Peaget, Erikson, and Rosseau.